Selected Processes in SMEs, Targeting to South Bohemia Region and Trade Sector - Monika Březinová; Jaroslav Vrchota (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2016)
Process management plays an important role in making up the competitiveness of small and medium-sized enterprises. This issue is researched in the long term at the Economic University of South Bohemia. The paper presents a comparison of trends in the average level of functioning of core processes (selling, human resources, marketing and finance) in the South Bohemian Region MSP for 3 years in the sector of trade. The first data was obtained under the grant GAJU 068/2010/S in 2010, and the second group of data was obtained from the grant GAJU 039/2013/S and GAJU 079/2013/S in 2013. From all the chosen processes within the research sample, significant changes can be shown only in the processes of human resources management and production where improvement of functioning of the processes was achieved. In the research project were used secondary data (financial statements of SMEs, who took part in the research and primary data which were obtained primarily through quantitative methods questionnaire supplemented by qualitative method of in-depth interviews.